2017
DOI: 10.1111/jace.15108
|View full text |Cite
|
Sign up to set email alerts
|

The fracture toughness of inorganic glasses

Abstract: To cite this version:Tanguy Rouxel, Satoshi Yoshida. The fracture toughness of inorganic glasses. Journal of the American Ceramic Society, Wiley, 2017, 100 (10), pp.4374-4396. <10.1111/jace.15108>. Accepted ArticleThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as doi: 10.11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
96
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 120 publications
(172 reference statements)
2
96
0
1
Order By: Relevance
“…Indentation thus mimics real‐life damage incidents under controlled conditions, requiring relatively small sample area and with short experiment time . However, we note that it is important to distinguish between resistance to crack initiation and crack growth, as high crack initiation resistance (which is measured by indentation) does not necessarily entail large fracture toughness . By studying different glass compositions, Peter showed that the deformation mechanism of oxide glasses to indentation in general includes both densification and shear flow .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indentation thus mimics real‐life damage incidents under controlled conditions, requiring relatively small sample area and with short experiment time . However, we note that it is important to distinguish between resistance to crack initiation and crack growth, as high crack initiation resistance (which is measured by indentation) does not necessarily entail large fracture toughness . By studying different glass compositions, Peter showed that the deformation mechanism of oxide glasses to indentation in general includes both densification and shear flow .…”
Section: Introductionmentioning
confidence: 90%
“…14,15 However, we note that it is important to distinguish between resistance to crack initiation and crack growth, as high crack initiation resistance (which is measured by indentation) does not necessarily entail large fracture toughness. 16 By studying different glass compositions, Peter showed that the deformation mechanism of oxide glasses to indentation in general includes both densification and shear flow. 17 Kato et al have shown that glass compositions prone to undergo densification during indentation can lower the residual stress acting as the driving force for cracking, since densification does not lead to an expansion of the plastic zone.…”
mentioning
confidence: 99%
“…As a widely used material, glass exhibits excellent optical properties and multifunctionalities, but its applications are limited by its low crack resistance due to the lack of large deformation or toughening mechanism at ambient temperature. [1][2][3] For most commercial glasses, the two properties, that is, hardness and crack resistance are not compatible. 4 Therefore, hard and tough glasses are particularly desired in many fields such as vehicles, civil engineering, and electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, microscale lattice materials, metamaterials, photonic crystals, nano‐electromechanical (NEMS) and micro‐electromechanical systems (MEMS) are taking advantage of sub‐micrometer‐scale feature size effects in 3D . In these contexts, fabrication of components based on ceramic materials would expand the range of properties offered by polymers currently used for 3D nanoscale fabrications, allowing for higher refractoriness, increased chemical durability, better wear and oxidation resistance, higher elastic modulus and improved dimensional stability with temperature …”
Section: Introductionmentioning
confidence: 99%